Development of DesignThinking Abilities - Boztay Z.B., Boztay Z.B.; Shukirzhan A.T. , Shukirzhan A.T. (Рroblems of engineering and professional education, 2022)
Each person wants to think creatively. Each company wants to sell products that are in demand. Therefore, for developing mind creativelythe roll of “Design thinking” is huge. There in article about design thinking will be given some tips from David Kelley who is considered as a father of design thinking. The idea of “design thinking” was first formulated by Herbert Simon in 1969 in his book “The Sciences of the Artificial” then he opened “D school” at Stanford University for developing design thinking among students. Moreover, in the article will be considered some tips for using design thinking by taking ideas from surrounding from the book “Steal like an artist” written by Austin Kleon. Furthermore, to promote design thinking in your workplace or between colleagues was given some advice from the book “Delivering Happiness: A Path to Profits, Passion, and Purpose» which was written by Tony Hsieh. Also design thinking widely used in Architectural design to build new modern buildings without damaging old ones. Design thinking exploited everywhere and anywhere where creativity and developing is used.